Trends in proportion of older HIV-infected people in care in Latin America and the Caribbean: a growing challenge. Issue 10 (30th May 2018) - Caro-Vega, Y.; Belaunzarán-Zamudio, P. F.; Crabtree-Ramírez, B.; Shepherd, B. E.; Mejia, F.; Giganti, M. J.; Patterson, P.; Grinsztejn, B.; Wolff, M.; Pape, J. W.; Padgett, D.; Castilho, J. L.; et al.
Abstract: We aimed to quantify the proportion of people receiving care for HIV-infection that are 50 years or older (older HIV patients) in Latin America and the Caribbean between 2000 and 2015 and to estimate the contribution to the growth of this population of people enrolled before (<50yo) and after 50 years old (yo) (⩾50yo). We used a series of repeated, cross-sectional measurements over time in the Caribbean, Central and South American network (CCASAnet) cohort. We estimated the percentage of patients retained in care each year that were older HIV patients. For every calendar year, we divided patients into two groups: those who enrolled before age 50 and after age 50. We used logistic regression models to estimate the change in the proportion of older HIV patients between 2000 and 2015. The percentage of CCASAnet HIV patients over 50 years had a threefold increase (8% to 24%) between 2000 and 2015. Most of the growth of this population can be explained by the increasing proportion of people that enrolled before 50 years and aged in care. These changes will impact needs of care for people living with HIV, due to multiple comorbidities and high risk of disability associated with aging.